Kryzys zadłużeniowy w strefie euro w latach 2010‑2018: Geneza, dynamika oraz instrumenty jego przezwyciężenia (Politeja, 2020)
The Debt Crisis in the Eurozone in Years 2010‑ 2018. Genesis, Dynamics and Tools to Overcome the CrisisThe global financial crisis significantly contributed to the outbreak of the Eurozone debt crisis in 2010 and exposed the institutional weaknesses of the entire zone that had existed since its inception. In 2010‑2018, the European Union focused essentially on four basic forms of crisis management in the Eurozone: financial support for indebted economies, aid programs for crisis‑stricken countries, measures by the European Central Bank to overcome the crisis and system reform of the Eurozone and the Economic and Monetary Union. The research objective of the article is to analyze the dynamics of the debt crisis in the Eurozone. The author would like to answer the following research questions: How much have the aid programs of the European Union and the International Monetary Fund contributed to overcoming the debt crisis? Has this crisis really been overcome? How deep were the structural reforms of the indebted economies? The author also defines the research hypothesis that the debt crisis in the Eurozone has not been finally overcome, since in many countries government debt is still on a high level.